Position of Woman according to 19th Century Montenegrin Marital Law - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Legal position of woman in 19th century Montenegrin marital law is examined in this paper. Provisions on entering into marriage, woman᾽s marital infidelity, legal separation, dissolution of marriage and its legal effects as well as widow᾿s property rights are scrutinized and critically analyzed. The author also indicates to rules of customary law regarding legal status of a married woman. Married woman had restricted legal capacity, as well as restricted property rights and no rights of succession. However, gender inequality common in patriarchal society such as Montenegrin in 19th century is particularly accentuated in case of marital infidelity. Only woman’s adultery is punishable and regarded as a serious crime. Beside marital infidelity, lower position of woman is noticeable in all aspects of married life. Hence, legislative attemps to improve woman᾿s legal status are emphasized in the article.